Stakeholder Engagement in the Translation of a Hypertension Control Program to Guatemala's Public Primary Health Care System: Lessons Learned, Challenges, and Opportunities - Fort, Meredith P. (2019)
Background: There is an urgent need to define appropriate intervention strategies to control blood pressure in low- and middle-income countries. In 2018, a program proven effective in Argentina was translated to Guatemala's public primary health care system in rural and primarily indigenous communities. Objectives: This paper describes the stakeholder engagement process used to adapt the program to the Guatemalan rural context prior to implementing a type II hybrid effectiveness-implementation trial and shares lessons learned. Methods: We identified key differences in the 2 contexts that are relevant to translating the intervention to the Guatemalan context. Alongside interviews and focus group discussions, we conducted consultation workshops in July and August 2018, applying a participatory translation process involving patients, family members, community members, health care providers, and Ministry of Health officials. The process consisted of multiple meetings in Guatemala City, as well as meetings in each of the 5 departments where the study will be implemented, and 1 district per department. During the workshops, we presented the evidence-based experience from Argentina and then focused on the challenges and recommended solutions that the participants identified for each of the intervention's 6 components. The process concluded with a meeting in which the research team and Ministry of Health officials defined specific details of the intervention. Results: The outcome of the process is an adapted approach appropriate to integrate into Guatemala's public primary health care system in the trial phase. The approach considers the challenges and recommended strategies for each of the 6 intervention components. Conclusions: We identified lessons learned, challenges, and opportunities during the adaptation process. Findings will inform ongoing stakeholder engagement during the study implementation and future scale-up and efforts to translate evidence-based hypertension control strategies to low- and middle-income countries globally.